Domination among tour operators in Karst conservation area of Goa Pindul, Indonesia. (10th May 2019) - Handoko, Victoria Sundari
The karst area of Goa Pindul has been 'commercially promoted' and exploited to meet the tourism demand. Goa Pindul becomes a space contested by tour operators. Domination among tour operators has created inequality in the community. This ethnographic research was conducted to investigate how competition and dominance occur among tour operators in tourism market. The results of this study indicate that the government should create the rules of the game in accordance with the ideal vision of the sustainable development of karst areas of Goa Pindul .